Analisis Faktor-Faktor Yang Mempengaruhi Penerapan Aplikasi Komputer Zakat Yang Digunakan Dalam Pengelolaan Zakat Pada Lazismu Universitas Muhammadiyah Surakarta - Ferdilla, Nurnita; , Dr. Agung Riyardi, M.Si (2017)
ABSTRACT This research aims at determining and analyzing the supporting factors which affect the tithe computerized application in managing tithe in Lazismu Muhammadiyah University of Surakarta. The type of the research is field research; it observes the problem from the actual object directly in order to gain some information. The approach of the research is descriptive qualitative; it firstly collects the data through interview and observation thus the researcher gets primary and secondary data then the researcher will employ qualitative analysis. Based on the finding of the research, it shows that the application in Lazismu Muhammadiah University of Surakarta uses excel program. In relation to the cost, it is quite cheap thus both the use of the program and the operational cost are not the obstacle factor. From the system point of view, the use of excel application program in Lazismu Muhammadiyah University of Surakarta is effective to meet the need of monetary service although it still uses a simple excel program. The human resource is another point of view which affect the application of the tithe since the excel program application depends on the soft skill of the operator. Another factor is customer or muzakki (Arabic) which plays less affect of the operational system of the tithe in Lazismu Muhammadiyah University of Surakarta. Keywords: performance, Lazismu Muhammadiyah University of Surakarta, efficiency, tithe management, tithe application